Biomechanical study of vertebral compression fracture using finite element analysis - Hiromitsu, Takano; Ikuho, Yonezawa; Mitsugu, Todo; Mazlan, Muhammad Hazli; Tatsuya, Sato; Kazuo, Kaneko (Scientific Research Publishing, 2017)
This research aimed to mechanically analyze vertebral stress concentration in one healthy subject and one subject with osteoporotic first lumbar (L1) vertebral compression fracture by using finite element analysis (FEA). We constructed three-dimensional image-based finite element (FE) models (Th12L2) by using computed tomographic (CT) digital imaging and communications in medicine (DICOM) for each patient and then conducted exercise stress simulations on the spine models. The loadings on the 12th thoracic vertebra (Th12) due to compression, flexion, extension, lateral bending, and axial rotation were examined within the virtual space for both spine models. The healthy and vertebral compression fracture models were then compared based on the application of equivalent vertebral stress. The comparison showed that vertebral stress concentration increased with all stresses in the vertebral compression fracture models. In particular, compression and axial rotation caused remarkable increases in stress concentration in the vertebral compression fracture models. These results suggest that secondary vertebral compression fractures are caused not only by bone fragility but possibly also by the increase in vertebral stress concentration around the site of the initial fracture